Pola Manajemen Pembelajaran Akidah Akhlaq Di MTs Negeri 6 Sleman - Ahmad Dwi Nur Khalim (Al-fahim : Jurnal Manajemen Pendidikan Islam, 2019)
This study aims to look at the pattern of management of moral learning. This research is a field research with a qualitative approach. The research subjects in this study were moral teachers and students of class VIII MTs N 6 Sleman. Data collection techniques through the method of observation , interview methods and documentation method. And analyzed with descriptive analysis method. The results of the analysis show the pattern of the management of moral learning in MTs N 6 sleman according to management functions namely Planning, Organizing, Actuating and Controlling. In organizing and actuating activities merge into one in the implementation phase. The pattern of management of moral learning in the MTs N 6 Sleman starts from the planning, implementation and controling. The existing problems include evaluation, media and the role of MGMP not yet maximized. The completion strategy includes tahfid activities / programs, using the environment as a learning medium and using many approaches in evaluation